2010
DOI: 10.1002/lary.21004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of laryngeal framework surgery: 10‐year follow‐up to a national survey

Abstract: Laryngeal framework surgeries are being performed with increasing frequency in the United States. The overall complication rate is slightly increased in the present study, but airway compromise and poor vocal outcome are decreased, and the need for revision surgery is unchanged. These findings suggest a continued high level of efficacy of these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
96
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 16 publications
12
96
2
5
Order By: Relevance
“…Medialization by thyroplasty is a ''gold standard'' for patients with glottic gap more than 3 mm. 1,2,23 CONCLUSION Vocal fold augmentation with Restylane can be offered to patients with UVP and dysphonia because of glottal gap who do not want definite surgery (such as thyroplasty). By closing the gap, subsequent speech therapy is made easier.…”
Section: Reiter Rudolf and Brosch Sibylle Laryngoplasty With Hyaluronmentioning
confidence: 99%
“…Medialization by thyroplasty is a ''gold standard'' for patients with glottic gap more than 3 mm. 1,2,23 CONCLUSION Vocal fold augmentation with Restylane can be offered to patients with UVP and dysphonia because of glottal gap who do not want definite surgery (such as thyroplasty). By closing the gap, subsequent speech therapy is made easier.…”
Section: Reiter Rudolf and Brosch Sibylle Laryngoplasty With Hyaluronmentioning
confidence: 99%
“…The response rate is similar to other mail-based survey studies. 22,23 A self-selection bias is likely to have occurred. Teachers with voice disorders may have been more likely to participate in the study, inflating results, such as the prevalence rates of dysphonia.…”
Section: Discussionmentioning
confidence: 99%
“…232 All procedures to rehabilitate UVFP are considered safe and effective with very high success rates documented. 225,[233][234][235][236] Few direct comparisons have suggested that one procedure is superior to another. 225 The surgeon must bear in mind that if there is concern regarding aggressive thyroid malignancy with possible or probable local recurrence requiring further treatment, it may be prudent to avoid further incisions in the neck with or without placement of foreign materials in that location.…”
mentioning
confidence: 99%